Elevated Serum Neuropeptide FF Levels Are Associated with Cognitive Decline in Patients with Spinal Cord Injury - Shifei Sun (Hindawi Limited, 2021)
Background. Spinal cord injury (SCI) has high incidence globally and is frequently accompanied by subsequent cognitive decline. Accurate early risk-categorization of SCI patients for cognitive decline using biomarkers can enable the timely application of appropriate neuroprotective measures and the development of new agents for the management of SCI-associated cognitive decline. Neuropeptide FF is an endogenous neuropeptide with a multitude of functions and is associated with neuroinflammatory processes. This prospective study investigated the predictive value of serum neuropeptide FF levels measured after acute SCI for subsequent cognitive decline. Methods. 88 patients presenting with acute SCI without preexisting neurological injury, brain trauma, or severe systemic illness and 60 healthy controls were recruited. Serum neuropeptide FF levels, clinical, and routine laboratory variables including low-density lipoprotein, high-density lipoprotein, fasting blood glucose, total triiodothyronine (TT3), total thyroxine (TT4), and thyroid-stimulating hormone (TSH) levels collected from all subjects were assessed. Montreal cognitive assessment (MoCA) was performed 3 months after enrollment. SCI patients were grouped according to quartile of serum neuropeptide FF level and MoCA scores were compared using ANOVA. Additionally, multivariate linear regression with clinical and laboratory variables was performed to predict MoCA scores. Results. SCI patients displayed significantly higher baseline serum neuropeptide FF levels than healthy controls (38.5±4.1 versus 23.4±2.0 pg/ml, p<0.001∗∗). SCI patients in higher quartiles of baseline serum neuropeptide FF displayed significantly lower MoCA scores at 3 months. Linear regression analysis indicated serum neuropeptide FF levels as a significant independent predictor of worse MoCA scores after SCI (r=0.331, p=0.034∗). Conclusion. Early serum neuropeptide FF levels significantly and independently predicted cognitive decline after acute SCI among patients without preexisting neurological disorders.